(untitled) (Research, Society and Development, 2022)
The objective of the study is to investigate the challenges experienced in teaching higher education by professors with a degree in Economic Sciences, at the beginning of their careers, understanding the perceptions of beginning teachers regarding the training needs to overcome the challenges of teaching in higher education, finally, the creation of the Index of Challenges for Economics Teachers at the Beginning of their Career – IDEIC. For this purpose, the quanti-qualitative research was used as a methodological approach. The sample is non-probabilistic, for convenience, and had 12 teachers, distributed in three northeastern states, namely: Piauí, Rio Grande do Norte and Ceará. The results show that the challenges faced are characterized in different aspects, since they range from the lack of initial training, pedagogical training and institutional support. The most direct conclusion of the study is that teachers have, mainly, gaps in Pedagogical Training and Initial Training, which contributed to the high value of IDEIC (0.86).